Nutrition Guide for Physicians and Related Healthcare Professionals - Temple, Norman J.; Wilson, Ted; Bray, George A. (Springer International Publishing : Imprint: Humana Press, 2017)
Nutrition Guide for Physicians is a desktop reference guide on nutrition and its clinical implications for health and disease through the lifecycle. Presented in a new softcover format and user-friendly style, it serves as a valuable resource of practical information on nutrition for physicians in their daily practice. Nutrition Guide for Physicians is divided into three parts that cross the spectrum of nutritional concerns for improving the practice of medicine. Part One provides basic nutritional principles for physicians. Part Two covers nutrition through the lifecycle and optimal nutrition patterns through all stages of development. Part Three covers diet and its role in prevention, cause and treatment of disease. All chapters include figures and tables that provide useful descriptive and visual reviews. "Key points" and succinct "conclusions" are also provided for each topic. Nutrition Guide for Physicians provides a wide perspective of the impact that nutrition has upon medical practice and will be am indispensable resource for primary care physicians and other medical professionals.
Keywords: Medicine.; Nutrition.; General practice (Medicine).; Health promotion.; Clinical nutrition.; Primary care (Medicine).; elektronické knihy; electronic books